Nursing of an elderly patient with esophageal food impaction during the recovery stage after cerebral infarction (1例老年脑梗死康复患者食物嵌塞的护理体会) - LIU Miao (刘苗); XU Bing (许冰); PENG Dan (彭丹) (Association of Integrative Nursing, 2023)
This paper summarized the nursing management for an elderly patient with esophageal food impaction during the recovery stage after cerebral infarction. Based on the nursing assessment on hospital admission, gastroscopy-assisted foreign body removal was carried out. Much attention has been paid on the perioperative nursing and health education about functional exercise after discharge from hospital. A systematic and comprehensive support was provided including dietary guidance, swallowing exercise, limb function exercise, language function exercise and psychological care. (本文总结1例老年脑梗死康复患者引起食物嵌塞的护理经验。在完善入院评估的基础上, 加强胃镜下食管异物取出围手术期护理, 开展出院后功能锻炼和延续护理指导, 从饮食、吞咽功能锻炼、肢体功能锻炼、语言功能锻炼及心理方面为患者及家属提供系统全面的护理干预。)